CEREBRAL PALSY: THE STATE OF KNOWLEDGE OF THE PROBLEM - Kattaeva Maftuna Dusyor kizi (Journals Park Publishing, 2025)
Based on the results of the analysis of scientific data, the understanding of the prevalence of cerebral palsy in Uzbekistan and abroad has been updated. The review describes the risk factors associated with the development of this pathology, indicates the main approaches to the classification of cerebral palsy, the characteristic clinical picture, and issues of diagnosis and treatment. Despite the presence of a large number of studies devoted to this issue, at this stage there is no consensus on the etiology and issues of early diagnosis remain unresolved to the end.
Keywords: Cerebral palsy, prevalence of pathology, risk factors, clinical picture.